S-BPM in the Production Industry A Stakeholder Approach - Neubauer, Matthias; Stary, Christian (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 4.0 license. This volume presents several case studies highlighting the latest findings in Industry 4.0 projects utilizing S-BPM features. Their potential is explored in detail, while the limits of engineering a company from a communication-centred perspective are also discussed. After a general introduction and an overview of the book in chapter 1, chapter 2 starts by condensing the industrial challenges driven by the German "Industry 4.0" trend to form a concrete vision for future production industries. Subsequently, chapter 3 introduces the basic concepts of S-BPM and its capabilities, in particular for supporting the restructuring of processes. The next three chapters then present various case studies, e.g. at an SME offering the production of atypical, unique and special purpose machinery, equipment and technologically complex units particularly useful in the automotive and electronic industries; and at a further SME producing highly-customized floor cleaning machines. Rounding out the coverage, the last two chapters summarize the achievements and lessons learned with regard to the road ahead. Overall, the book provides a realistic portrait of the status quo based on current findings, and outlines the future activities to be pursued in order to establish stakeholder-centred digital production systems. As such, developers, educators, and practitioners will find both the conceptual background and results from the field reflecting the state-of-the-art in vertical and horizontal process integration.